Програмне забезпечення інформаційної взаємодії з випускниками на прикладі кафедри СКІД - Пелещишин, Андрій; Паздерська, Руслана (Видавництво Львівської політехніки, 2017)
The article describes the major problems of employment students after graduation at university. Developed version of interaction by creating a database.
Keywords: graduates; cathedra; university; employer; lecturer; date base; information exchange; information interaction